Filipino and Thai Responses to Compliments in English - Boonkongsaen, Nathaya (Asian Health, Science and Technology Reports, 2011)
Cross-cultural differences in the content of compliment responses (CRs) have been extensively investigated, particularly in comparing CRs between the native and non-native speakers of English. However, research investigating the speech acts performed by non-native speakers of various linguistic and cultural backgrounds seems scarce. This study investigated CRs of Filipinos and Thais. The data were collected through the use of written discourse completion tasks (DCTs), with four situational settings (appearance, character, ability and possession). A total of 60 subjects participated in this study. There were 30 subjects in each group, one was Thai and the other was Filipino. All subjects were required to respond to the compliments in English. The overall findings of this study revealed significant differences between Filipino and Thai speakers. That is, Filipinos employed ‘Accept’ strategies more often than Thais while Thais tended to employ the ‘Combination’ strategies more than Filipinos. This study highlights that people from different cultural backgrounds have different sets of CRs. The findings also suggest the implications for language teaching so as to raise students’ awareness of conducting CRs in English.